Characteristics of Lower Back Pain in Pregnant Ladies in Thiqar-Iraq (Medico Legal Update, 2020)
Objectives: to evaluate the frequency of back pain among pregnant female in Thiqar province in Iraq and its demographic characteristics.Methodology: this is a case series descriptive study of one hundred pregnant female in Thiqar province in Iraq complaining from lower back pain in different stages of their pregnancies. the patients were evaluated firstly by history taking through questioner specially prepared for this study ;as well as; clinical and radiological assessment.Results: in our study seventy one patients experience back pain in different stages of pregnancy giving a (71%) as frequency of back pain in the studded group. Most of the patients Seventy four patients (74%) developed the pain during the first trimester of pregnancy and ( 22%) experience the pain during the second trimester. Fifty eight (14) patients (11.96%) gave history of previous back problems before pregnancy; of these; nine patients (7.69%) diagnosed before pregnancy as herniated lumbar disc prolapse and kept on medical treatment and physiotherapy, 2 patients (1.7%) with previous laminectomy surgeries for herniated lumbar disc prolapse, 3 patients (2.56) with diagnosis of degerative spine. One patient underwent cesarean section for sever back pain dueto lumbar disc prolapse at the end of the pregnancy period ( non-gynecological indication for cesarean section ).Conclusion: lower back pain is a common problem during pregnancy ,and it shows some common epidemiological characteristics.